The Effect of Self-Care Behavior on Blood Glucose Control Levels Among Patients with Type II Diabetes Mellitus - Helpianus Siswanto Hondro; Evi Karota; Riswani Tanjung; Zulhaida Lubis; Siti Zahara Nasution (Indonesian Journal of Global Health Research, 2025)
Diabetes mellitus is characterized by elevated blood glucose levels above normal, with random blood glucose levels ≥ 200 mg/dl and fasting blood glucose levels ≥ 126 mg/dl. This study employed a quantitative research method with a quasi-experimental design and an equivalent control group design approach. The study utilized power analysis with consecutive sampling techniques. Data collection techniques involved distributing questionnaires to 74 diabetes mellitus patients in the Onolalu Health Center Working Area, South Nias District. Data analysis techniques used independent t-test statistical analysis and presented in the form of a T-test table. The results of the study indicate that there is an influence of self-care behavior on blood sugar control levels in type II diabetes mellitus patients in the Onolalu Health Center Working Area, South Nias Regency, with a Sig. (2-tailed) of 0.024 < 0.05. Therefore, in the independent sample t-test, it can be concluded that the null hypothesis (HO) is rejected and the alternative hypothesis (Ha) is accepted. Thus, it can be concluded that there is a significant (statistically significant) difference between the average blood sugar levels of type II diabetes mellitus patients in the intervention group and the control group.